2012
DOI: 10.1016/j.jep.2011.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lecythis pisonis Camb. (Lecythidaceae) in a mouse model of pruritus

Abstract: These results clearly indicate the antipruritic effects of Lecythis pisonis leaves and suggest that this effect may be related to a stabilizing action on mast cell membrane. Furthermore, these data support the traditional use of this plant against cutaneous pruritus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
4
0
4
Order By: Relevance
“…Esses resultados estão em acordo com os dados fitoquímicos apresentados na literatura para a espécie. [15][16][17][18][19] Somente no extrato hexânico observou-se a formação de coloração verde na reação de Liebermann-Burchard, indicativo da presença de triterpenos e/ou esteroides. De acordo com Burke e colaboradores, 23 a mudança na coloração é devida a formação do carbocátion 3,5-colestadieno que absorve em torno de 410 nm.…”
Section: Triagem Fitoquímicaunclassified
See 2 more Smart Citations
“…Esses resultados estão em acordo com os dados fitoquímicos apresentados na literatura para a espécie. [15][16][17][18][19] Somente no extrato hexânico observou-se a formação de coloração verde na reação de Liebermann-Burchard, indicativo da presença de triterpenos e/ou esteroides. De acordo com Burke e colaboradores, 23 a mudança na coloração é devida a formação do carbocátion 3,5-colestadieno que absorve em torno de 410 nm.…”
Section: Triagem Fitoquímicaunclassified
“…A investigação fitoquímica dos extratos de baixa polaridade das folhas secas de L. pisonis, resultou na identificação da mistura dos triterpenos: epifriedelanol e friedelina (1+2), α-amirina e β-amirina (4+5) e esqualeno (3), da mistura dos esteroides: estigmasterol e β-sitosterol (6+7); α-tocoferol (8); e da mistura dos seguintes ésteres de cadeia longa: palmitato de metila, palmitato de etila, 9-octadecenoato de etila, 9,12,15-octadecanoato de metila, palmitato de butila, octadecanoato de etila e octadecanoato de butila (9)(10)(11)(12)(13)(14)(15). O fracionamento dos extratos de alta polaridade possibilitou a identificação do ácido ursólico (16) (21), ácido gálico (17) e do galato de metila (19). Do hidrolato resultante da extração das folhas frescas em destilador tipo Clevenger, foram identificados o ácido gálico (17) e o ácido elágico (18).…”
Section: Determinação Estrutural Das Substânciasunclassified
See 1 more Smart Citation
“…Several parts of sapucaia plants such as the leaves, shell, and oil are also used in popular medicine (Agra, Freitas, & Barbosa-Filho, 2007;Franco & Barros, 2006;Wickens, 1995). The antipruritic effects and antinociceptive activity of Lecythis pisonis leaves have been reported (Brandão et al, 2013;Silva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical study of the leaves of this species led to the isolation of pentacyclic triterpenoids, phytol, sitosterol and stigmasterol (Oliveira et al, 2012). The ethanol extract and the mixture of ursolic and oleanolic acids obtained from the leaves demonstrated antipruritic and cytotoxic activities (Silva et al, 2012;Oliveira et al, 2012). Other studies also showed that ethanol extract, eterea fraction and mixture of ursolic and oleanolic acids from leaves of L. pisonis exhibited antinociceptive activity in models of acute pain in mice (Brandão et al, 2013).…”
Section: Introductionmentioning
confidence: 99%